2018
DOI: 10.1103/physrevb.97.161109
|View full text |Cite
|
Sign up to set email alerts
|

Formation of an incoherent metallic state in Rh-doped Sr2IrO4

Abstract: Sr2IrO4 is the archetype of the spin-orbit Mott insulator, but the nature of the metallic states that may emerge from this type of insulator is still not very well known. We study with angle-resolved photoemission the insulator-to-metal transition observed in Sr2Ir1−xRhxO4 when Ir is substituted by Rh (0.02 < x < 0.35). The originality of the Rh doping is that Ir and Rh, which are formally isovalent, adopt different charge states, a rather unusual and inhomogeneous situation. We show that the evolution to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
38
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 33 publications
(60 reference statements)
12
38
3
Order By: Relevance
“…No sign of a gap formation is seen here down to the lowest temperature and frequency measured. Below the lower limit of our measurement of ∼ 10 meV, there may still be a pseudogap, as it has been observed in ARPES experiments [22,32]. Indeed, the dc resistivity data [40] are consistent with a decrease of the conductivity below ∼ 10 meV.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…No sign of a gap formation is seen here down to the lowest temperature and frequency measured. Below the lower limit of our measurement of ∼ 10 meV, there may still be a pseudogap, as it has been observed in ARPES experiments [22,32]. Indeed, the dc resistivity data [40] are consistent with a decrease of the conductivity below ∼ 10 meV.…”
supporting
confidence: 75%
“…Whereas Rh should be isovalent to Ir, it has been shown that the smaller SOC of Rh, as compared to Ir, gives rise to a charge transfer between neighbouring Ir and Rh ions, and thus an effective hole doping [22]. A corresponding shift of the chemi-cal potential in Sr 2 Ir 1−x Rh x O 4 was observed by angleresolved-photoemission spectroscopy (ARPES) [22,32] which suggest that the IMT occurs around x = 0.04 [22]. On the other hand, magnetization and neutron diffraction measurements establish that the AF transition temperature decreases more gradually and persists up to x ∼ 0.15 [22,23,[35][36][37][38][39].…”
mentioning
confidence: 99%
“…O K edge XAS spectra of pure, 15% Rh-, and 4% La-doped Sr 2 IrO 4 are shown in Fig.8, for two incident angles θ = 90 • (NI) and 20 • (GI). Rh-doping induces holes 10,18,28 , while La dopes with electrons 8,9 . These two different ways of doping move both compounds close to a metallic state 8 .…”
Section: La-and Rh-doped Sr2iro4mentioning
confidence: 99%
“…To our knowledge Rh doping, which substitutes for Ir, was never reported in Sr 3 Ir 2 O 7 . We show it induces effective hole doping as it does in Sr 2 IrO 4 [19][20][21][22] . Previous ARPES studies have well documented the emerging FS under high La doping, characterized by small "lens-like" electron pockets around the M point 13,14,23 .…”
Section: Introductionmentioning
confidence: 99%